Carbon nanotube pellicle film, pellicle, exposure plate, exposure apparatus, and method for manufacturing carbon nanotube pellicle film
Patent Information
- Application Number
- JP2025060011
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0008】 本開示の一態様によれば、膜減りのばらつきが抑制されたカーボンナノチューブペリクル膜及びその製造方法、並びに該カーボンナノチューブペリクル膜を用いたペリクル、露光原版、及び露光装置が提供される。 また、膜減り及びそのばらつきが抑えられることで、ペリクル膜の長寿命化が期待できる。
Smart Images

Figure 2026166812000007 
Figure 2026166812000008 
Figure 2026166812000009
Abstract
Description
[Technical Field]
[0001] This disclosure relates to a carbon nanotube pellicle film, a pellicle, an exposure plate, an exposure apparatus, and a method for manufacturing a carbon nanotube pellicle film. [Background technology]
[0002] Miniaturization of semiconductor integrated circuits is being driven by photolithography. In recent years, with the increasing resolution of semiconductor integrated circuits, EUV (Extreme Ultraviolet) light has been used. Because of its short wavelength, EUV light is easily absorbed by gases, liquids, and solids. Therefore, in exposure methods using EUV light, a photomask equipped with a reflective layer that reflects EUV light is used, and the photomask and optical system are installed in a vacuum chamber. Exposure using EUV light (hereinafter referred to as "exposure light") is performed in a vacuum atmosphere.
[0003] Various studies have been conducted on photolithography using EUV. For example, Patent Document 1 discloses a mask assembly suitable for use in a lithography process, comprising: a patterning device; (a) a pellicle frame configured to support a pellicle and mounted on the patterning device using a mount; and (b) a pellicle frame, the mount configured to suspend the pellicle frame from the patterning device such that a gap exists between the pellicle frame and the patterning device, wherein the mount provides a removablely engageable attachment between the patterning device and the pellicle frame. [Prior art documents] [Patent Documents]
[0004] [Patent Document 1] Japanese Patent Publication No. 2020-181212 [Overview of the Initiative] [Problems that the invention aims to solve]
[0005] The pellicle film that protects photomasks from dust may wear down when exposed to hydrogen plasma generated by EUV irradiation. This wear can vary from film to film, and it is essential that the pellicle film suppresses this variation. By suppressing both the wear and its variation, a longer and more stable lifespan for the pellicle film can be expected.
[0006] One object of one aspect of this disclosure is to provide a carbon nanotube pellicle film in which variations in film thinning are suppressed, a method for manufacturing the same, and a pellicle, exposure master, and exposure apparatus using the carbon nanotube pellicle film. [Means for solving the problem]
[0007] The means for solving the above problems include the following embodiments. <1> Contains multiple carbon nanotubes, The etching rate when dry etching is performed using hydrogen plasma is 0.40 nm / min or less. Carbon nanotube pellicle membrane. <2> The content of single-walled carbon nanotubes is 70% by mass or less of the total amount of carbon nanotubes. <1> The carbon nanotube pellicle membrane described above. <3> In the Raman spectrum of a carbon nanotube pellicle film, the G / D ratio, which is the ratio of the intensity of the G band to the intensity of the D band, is 40 or greater. <1> or <2> The carbon nanotube pellicle membrane described above. <4> Contains multiple carbon nanotubes, In the Raman spectrum of a carbon nanotube pellicle film, the G / D ratio, which is the ratio of the intensity of the G band to the intensity of the D band, is 40 or greater. The content of single-walled carbon nanotubes is 70% by mass or less of the total amount of carbon nanotubes. A carbon nanotube pellicle film. <5> A pellicle comprising: the carbon nanotube pellicle film according to any one of <1> to <4>; and a pellicle frame supporting the carbon nanotube pellicle film. <6> A photomask, and the pellicle according to <5> attached to the photomask , the exposure original plate comprising the same. <7> An EUV light source that emits EUV (extreme ultraviolet light) as exposure light, the exposure original plate according to <6>, and an optical system that guides the exposure light emitted from the EUV light source to the exposure original plate , the exposure apparatus comprising the same, wherein the exposure original plate is arranged such that the exposure light emitted from the EUV light source passes through the carbon nanotube pellicle film and is irradiated onto the photomask. <8> A method for producing a carbon nanotube pellicle film, comprising a mixing step of mixing a plurality of carbon nanotubes and a solvent to obtain a dispersion liquid, wherein in the Raman spectrum of the carbon nanotubes, the G / D ratio represented by the ratio of the intensity of the G band to the intensity of the D band is 200 or more. <9> The method for producing a carbon nanotube pellicle film according to <8>, wherein using the G / D ratio of the carbon nanotubes represented by the ratio of the intensity of the G band to the intensity of the D band in the Raman spectrum of the carbon nanotubes, and the G / D ratio of the carbon nanotube pellicle film represented by the ratio of the intensity of the G band to the intensity of the D band in the Raman spectrum of the carbon nanotube pellicle film, the G / D ratio reduction rate calculated by the following formula (2) is 85 or less. Formula (2): G / D ratio reduction rate = {(G / D ratio of carbon nanotubes) - (G / D ratio of carbon nanotube pellicle film)} × 100 / (G / D ratio of carbon nanotubes) [Advantageous Effects of the Invention]
[0008] According to one aspect of the present disclosure, there are provided a carbon nanotube pellicle film with suppressed variation in film thinning, a method for producing the same, as well as a pellicle, an exposure master plate, and an exposure apparatus using the carbon nanotube pellicle film. In addition, by suppressing film thinning and its variation, a longer service life of the pellicle film can be expected. [Brief Description of the Drawings]
[0009] [Figure 1] Figure 1 is a diagram showing a model of air layer / NT film layer / silicon substrate. [Figure 2] Figure 2 is a graph plotting the relationship between reflectance and film thickness, for a sample in which a non-uniform NT film is transferred onto a silicon substrate, when the reflectance at a wavelength of 285 nm and the film thickness are measured by the method described above. [Figure 3] Figure 3 is a top view of the pellicle according to the embodiment. [Figure 4] Figure 4 is a cross-sectional view taken along line IV-IV in Figure 3. [Figure 5] Figure 5 is a graph showing the correlation of G / D-etching rate in the examples. [Mode for Carrying Out the Invention]
[0010] In the present disclosure, "~" indicating a numerical range is used to mean that the numerical values stated before and after it are included as the lower limit value and the upper limit value. In the numerical ranges described stepwise in the present disclosure, the upper limit value or the lower limit value described in one numerical range may be replaced with the upper limit value or the lower limit value of another stepwise described numerical range. In the numerical ranges described in the present disclosure, the upper limit value or the lower limit value of the numerical range may be replaced with the values shown in the examples. In the present disclosure, the term "process" is included in this term not only as an independent process but also even when it cannot be clearly distinguished from other processes, as long as the intended purpose of the process is achieved. In this disclosure, when referring to the amount of each component in a composition, if there are multiple substances corresponding to each component in the composition, it means the total amount of all substances present in the composition unless otherwise specified. In this disclosure, "carbon nanotube pellicle film" refers to a pellicle film containing multiple carbon nanotubes. In this disclosure, "extreme ultraviolet light" (hereinafter also referred to as "EUV" or "extreme ultraviolet") refers to light with a wavelength of 1 nm or more and 30 nm or less. The wavelength of EUV is preferably 5 nm to 13.5 nm.
[0011] [Carbon nanotube pellicle membrane] <First carbon nanotube pellicle membrane> One embodiment of the carbon nanotube pellicle membrane of this disclosure (hereinafter also referred to as the "first CNT pellicle membrane") is, It contains multiple carbon nanotubes (hereinafter also referred to as "CNTs"), The etching rate when dry etching is performed using hydrogen plasma is 0.40 nm / min or less. In the section titled "<First Carbon Nanotube Pellicle Membrane>", the "first CNT pellicle membrane" is also simply referred to as the "CNT pellicle membrane".
[0012] Because the first CNT pellicle film has the above-described structure, variations in film loss between individual pellicle films are suppressed.
[0013] In this disclosure, "variation in film thinning" refers to the variation in film thinning that occurs for each CNT pellicle due to EUV irradiation in multiple manufactured CNT pellicles. Specifically, the "variation in film thinning" in this disclosure can be confirmed using the etching rate, which is evaluated in the examples described later, as an indicator. Larger fluctuations in the etching rate mean that the variation in film thinning is larger.
[0014] The reason why the first CNT pellicle membrane produces the above effect is not entirely clear, but it is presumed to be as follows. The inventors have found that CNT pellicle films exhibiting the above-mentioned etching rate are easily obtained by using CNTs with a large G / D ratio, which is expressed as the ratio of the intensity of the G band to the intensity of the D band in the Raman spectrum, as raw material, and that variations in film thinning are easily suppressed in CNT pellicle films obtained using such CNTs as raw material. In other words, it is presumed that variations in film thinning can be suppressed in CNT pellicle films exhibiting the above-mentioned etching rate.
[0015] (Carbon nanotubes) The CNT pellicle film contains multiple carbon nanotubes (CNTs). CNTs have high mechanical strength. Therefore, the mechanical strength of the CNT pellicle film is higher than that of a pellicle film made of SiN or polysilicon.
[0016] The CNT pellicle membrane may, if necessary, contain components other than CNTs (for example, fibers other than CNTs), and may be composed of multiple CNTs. Furthermore, the CNTs contained in the CNT pellicle membrane may be of one type alone, or two or more types may be used in combination.
[0017] CNTs may be single-walled carbon nanotubes (hereinafter also referred to as "single-walled CNTs") or multi-walled carbon nanotubes (hereinafter also referred to as "multi-walled CNTs").
[0018] In this disclosure, "single-walled carbon nanotube" refers to a single-walled CNT, and "multi-walled carbon nanotube" refers to a multi-walled CNT.
[0019] Multiple carbon nanotubes (CNTs) typically form bundles. The number of CNTs forming a bundle is three or more, preferably 4 to 100, and more preferably 5 to 50. The CNT pellicle film may also contain CNTs that are not bundled.
[0020] The tube diameter (i.e., the width of the CNT) is not particularly limited, but is preferably between 0.8 nm and 6.0 nm. This allows the CNT pellicle film to form a tougher film by forming a strong bundle compared to when the tube diameter of the CNT is outside the range of 0.8 nm to 6.0 nm. From the viewpoint of film strength, the tube diameter of the CNT is preferably 0.9 nm or larger, more preferably 1.0 nm or larger. From the viewpoint of film strength, the tube diameter of the CNT is preferably 5.0 nm or smaller, more preferably 5.5 nm or smaller.
[0021] The length of the CNTs is preferably 10 nm or more, and more preferably 100 nm or more. A CNT length of 10 nm or more allows the CNTs to intertwine well, resulting in excellent mechanical strength of the CNT pellicle film. The length of the CNTs is preferably 10 cm or less, more preferably 1 cm or less, and even more preferably 100 μm or less. From these viewpoints, the length of the CNTs is preferably 10 nm to 10 cm, more preferably 10 nm to 1 cm, and even more preferably 10 nm to 100 μm.
[0022] The outer diameter and length of the CNT tubes are determined by the arithmetic mean of values measured for 20 or more CNTs (primary particles) using electron microscopy. As for electron microscopes, scanning electron microscopes (SEM) or transmission electron microscopes (TEM) can be used.
[0023] The content of multiple CNTs is not particularly limited. The content of multiple CNTs is preferably 80% to 100% by mass, more preferably 90% to 100% by mass, even more preferably 95% to 100% by mass, and may be 100% by mass, relative to the total amount of the CNT pellicle film.
[0024] The content of single-walled carbon nanotubes (WYSNs) among the multiple CNTs is not particularly limited, but from the viewpoint of improving the thermal and chemical stability of the CNT pellicle film, it is preferably 70% by mass or less, more preferably 65% by mass or less, and may also be 50% by mass or less, 30% by mass or less, or 10% by mass or less, based on the total amount of multiple CNTs. The lower limit of the single-walled carbon nanotube content described above is not particularly limited, but it may be greater than 0% by mass, 1% or more by mass, or 3% or more by mass.
[0025] -Method for evaluating the content of single-walled carbon nanotubes (WYNTs) in multiple CNTs- The evaluation of the single-walled carbon nanotube (WYST) content among the multiple CNTs mentioned above (hereinafter also referred to as the "WYST ratio") is performed by observing and reading CNTs (primary particles) contained in an area of 3 μm × 3 μm with 60 or more CNTs within a field of view of less than 50 nm × 50 nm using an electron microscope. Specifically, it is determined whether each CNT is single-walled or not, and the WYST content is calculated as the percentage of the total amount of observed CNTs. As for electron microscopes, scanning electron microscopes (SEM) or transmission electron microscopes (TEM) can be used.
[0026] In the Raman spectrum of carbon nanotubes (specifically, the Raman spectrum using carbon nanotubes as raw materials), the G / D ratio, which is expressed as the ratio of the intensity of the G band to the intensity of the D band, is not particularly limited. However, from the viewpoint of suppressing variations in film thinning, it is preferably 200 or more, more preferably 230 or more, even more preferably 250 or more, and even more preferably 280 or more. The upper limit of the G / D ratio in the Raman spectrum of the carbon nanotube pellicle film described above may be, for example, 800 or less, 700 or less, 600 or less, 500 or less, or 400 or less. The above G / D ratio is a value that affects the level of crystallinity, as will be explained later. Therefore, for example, the above G / D ratio can be controlled by adjusting the crystallinity of the raw material CNT. Specifically, by using a material that can dissolve the less crystallinity portion, the overall crystallinity of the CNT can be improved, thereby increasing the above G / D ratio.
[0027] "D-band strength" refers to the D-band (1360 cm²) derived from the defect structure of the graphite structure (SP2 bond). -1 This shows the peak intensity (around 1580 cm²). "G-band intensity" refers to the G-band (1580 cm²) derived from the graphite structure (SP2 bonds). -1 This shows the peak intensity (near the specified value). The "ratio (G / D)" quantitatively indicates the degree of defect structure in the CNTs. It is thought that hydrogen plasma initiates the etching reaction of CNTs (i.e., decomposes and removes CNTs) starting from nanoscale defect structures on the surface of the CNTs. A higher ratio (G / D) indicates higher crystallinity of the CNTs constituting the CNT pellicle film (in other words, that no defect structures have occurred in the CNTs). Therefore, the higher the ratio (G / D), the less easily the CNTs are etched by hydrogen plasma.
[0028] -Method for measuring the G / D ratio of carbon nanotubes- A sample consisting of CNTs mounted on a Si wafer is placed in a Raman microscope (for example, XploRA manufactured by Horiba, Ltd.) and measured using a laser wavelength of 532 nm. From the obtained peaks, the G / D ratio is calculated from the intensities of the G band and D band, and this is defined as the G / D ratio of the CNT. The intensity of the D band and the intensity of the G band, respectively, are measured values obtained by Raman imaging using the above-mentioned sample. The strength of the D band is when the Raman shift is 1300 cm. -1 ~1400cm -1 This is the maximum value of Raman scattering intensity within the specified range. The intensity of the G-band is when the Raman shift is 1550 cm. -1 ~1610cm -1This is the maximum value of Raman scattering intensity within the specified range.
[0029] (Other ingredients) The CNT pellicle membrane may contain components other than CNTs (hereinafter also referred to as "other components"). Other components may include known components that can be contained in the CNT pellicle membrane (for example, fibers different from CNTs), or components that can be contained in the CNT dispersion used in the production of the CNT pellicle membrane. For example, the dispersion used in the production of the CNT pellicle membrane preferably contains a dispersant as another component, and the CNT pellicle membrane may also contain a dispersant.
[0030] The content of other components is not particularly limited. The content of other components is preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less, relative to the total amount of the CNT pellicle film, and may also be 0% by mass, 1% by mass or more, or 2% by mass or more.
[0031] (shape) The CNT pellicle membrane is a sheet-like material. The shape of the CNT pellicle membrane can be, for example, rectangular (e.g., rectangular or square), circular, or elliptical.
[0032] The size of the main surface of the CNT pellicle membrane is not particularly limited. On the main surface of the CNT pellicle membrane, the length in the first direction is 90 mm or more, and the length in the second direction perpendicular to the first direction may be 90 mm or more. The length in the first direction may be 100 mm or more, 300 mm or less, or 200 mm or less. The length in the first direction may be between 90 mm and 300 mm. The length in the second direction may be the same as the example given for the length in the first direction. The length in the second direction may be the same as or different from the length in the first direction.
[0033] (film thickness) The thickness of the CNT pellicle film is not particularly limited, but is preferably between 2 nm and 100 nm. This makes the CNT pellicle film less prone to damage and helps prevent foreign matter from adhering to the photomask compared to when the film thickness is outside the 2 nm to 100 nm range. From the viewpoint of preventing damage to the CNT pellicle film while preventing foreign matter from adhering to the photomask, the thickness of the CNT pellicle film is more preferably 3 nm or more, even more preferably 4 nm or more, and even more preferably 6 nm or more. From the viewpoint of increasing the transmittance of EUV (Extreme Ultra Violet) light, the thickness of the CNT pellicle film may be 100 nm or less, or 80 nm or less.
[0034] -Method for measuring film thickness- The thickness of the CNT pellicle film can be determined by measuring the reflectance using a reflectance spectrophotometer. However, the measurement conditions for the reflectance are as follows: -conditions- Diameter of measurement point: 20 μm For film thickness less than 40 nm: Measurement wavelength: 200 nm to 600 nm (wavelength interval: 1.3 nm to 1.5 nm) For film thickness of 40 nm or more: Measurement wavelength: 300 nm to 1000 nm (wavelength interval: 1.3 nm to 1.5 nm)
[0035] The film thickness at each measurement point is calculated using the method described in "Method for Converting Film Thickness (Optical Thickness)" below. The film thickness at each measurement position is also calculated. The average value of the calculated film thicknesses at each measurement position is defined as the "CNT pellicle film thickness". Similarly, the σ of the film thickness at each measurement position is calculated from the standard deviation of the film thicknesses at each measurement point.
[0036] The method for detecting reflected light in measuring film thickness is not particularly limited. A photodiode or a photomultiplier tube may be used to measure film thickness. A multi-channel detector (for example, a photodiode array or a CCD (Charge Coupled Device)) may be used to measure the film thickness. By detecting the spectrally separated reflected light with a photodiode array, reflectance at multiple wavelengths can be obtained. Alternatively, the pixel size of the CCD detector can be adjusted to approximately 50 μm to 100 μm to measure the distribution of reflected light intensity.
[0037] -Method for converting to film thickness (optical thickness)- First, a CNT pellicle film is placed on a silicon substrate, and the diagonal of the placed CNT pellicle film is defined as the X-axis. When placing a CNT pellicle film on a silicon substrate, the silicon substrate and the CNT pellicle film must be in close contact without any gaps. By placing a solvent (e.g., water, organic solvent, etc.) between the silicon substrate and the CNT pellicle film, and then drying the solvent, the silicon substrate and the CNT pellicle film can be made to adhere tightly without any gaps. For example, a CNT pellicle film floating on the water surface can be scooped up with a silicon substrate and then dried. Alternatively, by placing the CNT pellicle film on a silicon substrate containing a solvent and drying it, the silicon substrate and the CNT pellicle film can be made to adhere closely together. If the pellicle film is attached to the pellicle frame, it is also possible to prepare a silicon substrate moistened with a solvent, etc., and bring the portion of the CNT pellicle film corresponding to the self-supporting film region (i.e., the region not in contact with the pellicle frame) into contact with the silicon substrate, thereby positioning the CNT pellicle film on the silicon substrate. The size of the silicon substrate is not particularly limited. However, from the viewpoint of adhering a large area of CNT pellicle film to it, the silicon substrate is preferably a silicon wafer of 8 inches or larger.
[0038] As the reflectance measurement apparatus, a microspectroscopic film thickness meter (for example, OPTM manufactured by Otsuka Electronics Co., Ltd., model: A-1) is used, as the lens, for example, a reflective 10x lens is used, and as the apparatus for adjusting the diameter of the measurement point, an aperture with a diameter of 200 μm (diameter of the measurement point: 20 μm) is used respectively. Further, an aluminum substrate is used as a reference for reflection intensity measurement. The reflectance Rs(λ) is determined by the following formula.
[0039] [Equation]
[0040] Here, I s (λ) represents the reflection intensity of the CNT pellicle film on the silicon substrate at the wavelength λ. I ref (λ) represents the reflection intensity of the reference. R ref (λ) represents the absolute reflectance of the reference. When aluminum is used as the reference, since the optical constants of aluminum are known, R ref (λ) can be determined by calculation. Note that in the reflection intensity measurement of the reference and the CNT pellicle film on the silicon substrate, the gain, exposure time, and the like are under the same conditions. Thereby, the absolute reflectance of the CNT pellicle film on the silicon substrate can be obtained.
[0041] For each measurement point, a reflectance spectrum in the wavelength range of 200 nm to 600 nm is acquired at a wavelength interval in the range of 1 nm to 2 nm. Then, using the values of the optical constants (refractive index: n, extinction coefficient: k) shown in Table 2 as the optical constants of the CNT pellicle film, and using a three-layer model of air layer / CNT pellicle film layer / silicon substrate, the reflectance spectrum in the wavelength range of 225 nm to 500 nm is analyzed by the least squares method, to calculate the film thickness at each measurement point. The film thickness at the "measurement position" is defined as the average value of the film thicknesses of 121 measurement points included in the "measurement position". The following describes a method for calculating the film thickness at each measurement point by analyzing the reflectance spectrum in the wavelength range of 225 nm to 500 nm using the least squares method.
[0042] The film thickness is calculated using a three-layer model consisting of an air layer, a CNT pellicle film layer, and a silicon substrate, using the following relational equations (a) to (c). Figure 1 is a schematic diagram showing a model of an air layer / CNT pellicle film layer / silicon substrate.
[0043] Reflectance R s is the amplitude reflectance r s It can be expressed using the following equation (a).
[0044]
number
[0045] In the above formula, * represents the complex conjugate.
[0046] Amplitude reflectance r from three layers: air layer / CNT pellicle film layer / silicon substrate s This can be expressed by the following equation (b).
[0047]
number
[0048] In the above formula, r 01 r represents the amplitude reflectance from the interface between the air layer and the CNT pellicle film layer. 12 This represents the amplitude reflectance from the interface between the CNT pellicle film layer and the silicon substrate. i represents the imaginary unit. In the above equation, δ is the phase difference that occurs when light of wavelength λ travels back and forth through the film once, and is expressed by the following equation (c).
[0049]
number
[0050] In the above formula, d represents the film thickness, N represents the complex refractive index (N=n-ik), φ represents the angle of incidence, and i represents the imaginary unit.
[0051] The film thickness can be obtained by using the relationship given by equations (a) to (c) above, with the film thickness d as a variable for the reflectance Rs in the wavelength range of 225 to 500 nm, and calculating it by the least squares method.
[0052] Figure 2 is a graph plotting the relationship between reflectance and film thickness when the reflectance and film thickness at a wavelength of 285 nm were measured using the method described above for a sample in which a non-uniform CNT pellicle film was transferred onto a silicon substrate. As shown in Figure 2, the method described above allows for accurate determination of differences in film thickness based on reflectance values.
[0053] Table 1 shows specific examples of wavelength (nm), n, and k.
[0054] [Table 1]
[0055] (Antioxidant layer) The CNT pellicle film may include an antioxidant layer. The antioxidant layer is laminated on at least one main surface of the CNT pellicle film. This suppresses oxidation of the CNT pellicle film during EUV irradiation or pellicle storage.
[0056] The material of the oxidation-preventive layer is not particularly limited as long as it is a material that is stable against EUV. For example, the material of the oxidation-preventive layer is SiO x (x≦2), Si x N y (x / y is 0.7~1.5), examples include SiON, Y2O3, YN, Mo, Ru, Rb, Sr, Y, Zr, Nb, and Rh.
[0057] The thickness of the antioxidation layer is preferably 1 nm to 10 nm, more preferably 2 nm to 5 nm, from the viewpoint of suppressing the absorption of EUV by the antioxidation layer and suppressing the decrease in the EUV transmittance of the CNT pellicle film.
[0058] (Etching rate of CNT pellicle film) The etching rate when dry etching a CNT pellicle film with hydrogen plasma is 0.40 nm / min or less, preferably 0.38 nm / min or less, more preferably 0.36 nm / min or less, even more preferably 0.34 nm / min or less, and even more preferably 0.32 nm / min or less, from the viewpoint of suppressing variations in film thinning and ensuring a sufficient number of uses for the pellicle film. The etching rate described above is preferable as it is low, and there is no particular lower limit to it, but it may be 0.05 nm / min or higher, 0.1 nm / min or higher, 0.15 nm / min or higher, or 0.2 nm / min or higher. The above etching rate range can be achieved, for example, by increasing the G / D ratio in the Raman spectrum of the CNTs described above.
[0059] -Method for evaluating etching rate- The etching rate of a CNT pellicle film when dry-etched with hydrogen plasma can be evaluated using a parallel-plate type plasma processing apparatus (e.g., Yamato Scientific Co., Ltd., PDC-210) and the CNT pellicle film after measuring the thickness of the self-supporting film portion before hydrogen plasma irradiation. The method for measuring the film thickness of the self-supporting film portion before hydrogen plasma irradiation is the method described in the "Method for Measuring Film Thickness" section above. The film thickness of the following CNT pellicle films irradiated for 20 minutes, 30 minutes, and 40 minutes is measured using the same method. The following details the method for evaluating the etching rate mentioned above.
[0060] -Fabrication of CNT pellicle film irradiated for 20 minutes, and measurement of film thickness- First, the self-supporting portion of the CNT pellicle film, after measuring its thickness before hydrogen plasma irradiation, is exposed to the hydrogen plasma. This exposes the self-supporting portion to a hydrogen plasma environment similar to that of EUV exposure, causing etching and chemical changes in the self-supporting portion. Etching of the self-supporting portion due to exposure to hydrogen plasma results in a decrease in film thickness. Specifically, a CNT pellicle film is placed on an anode electrode (250 mm x 170 mm), vacuumed for 10 minutes, then hydrogen gas is flowed at 200 Pa for 5 minutes, and then hydrogen plasma irradiation is performed for 20 minutes according to the following hydrogen plasma treatment conditions. This yields a 20-minute irradiated CNT pellicle film.
[0061] -Hydrogen plasma treatment conditions- Chamber vacuum level: Pressure < 1 Pa Material gas: H2 (G1 grade) Processing pressure: 200 Pa (1.5 Torr) RF power: 100W Discharge frequency: 13.56MHz Electrode temperature: Room temperature (no heating)
[0062] Next, the thickness of the self-supporting portion of the CNT pellicle film irradiated for 20 minutes is measured.
[0063] -Fabrication of CNT pellicle film after 40 minutes of irradiation, and measurement of film thickness- Next, the 20-minute irradiated CNT pellicle film is irradiated with hydrogen plasma again using the same method as for obtaining the 20-minute irradiated CNT pellicle film, except that the hydrogen plasma irradiation time is changed to 10 minutes. This results in a 30-minute irradiated CNT pellicle film that has been irradiated with hydrogen plasma for a total of 30 minutes. Then, the thickness of the self-supporting portion of the 30-minute irradiated CNT pellicle film is measured. Furthermore, using the same method, the 30-minute irradiated CNT pellicle film is subjected to another 10-minute hydrogen plasma irradiation. This results in a 40-minute irradiated CNT pellicle film that has been irradiated with hydrogen plasma for a total of 40 minutes. Next, the thickness of the self-supporting portion of the 40-minute irradiated CNT pellicle film is measured.
[0064] -Calculation of etching rate- Using the measured thickness of the self-supporting film before hydrogen plasma irradiation (hereinafter referred to as "pre-irradiation film thickness") and the measured thickness of the self-supporting film after 20 minutes, 30 minutes, and 40 minutes of hydrogen plasma irradiation, respectively (hereinafter, the measured thickness of the self-supporting film after X minutes of irradiation is referred to as "post-irradiation film thickness (after X minutes)"), the amount of film loss at each irradiation time (hereinafter, the amount of film loss of the self-supporting film after X minutes of irradiation is referred to as "film loss after X minutes of irradiation") is calculated using the following formula (1). A low film loss indicates that etching of the self-supporting film by hydrogen plasma is small. Equation (1): Film thickness after irradiation (X minutes) (nm) = Film thickness before irradiation (nm) - Film thickness after irradiation (X minutes) (nm)
[0065] Furthermore, the etching rate is calculated using the post-irradiation film thickness (after X minutes) obtained by equation (1) above. Specifically, a graph is created with the hydrogen plasma irradiation time (X = 0 minutes, 20 minutes, 30 minutes, 40 minutes) on the X axis and the post-irradiation film thickness (Y = 0 (nm), film loss after 20 minutes (nm), film loss after 30 minutes (nm), film loss after 40 minutes (nm)) on the Y axis. The slope of the approximated line is calculated by approximating this graph with a straight line using the least squares method. This slope of the approximated line is taken as the etching rate.
[0066] (G / D ratio of CNT pellicle membrane) In the Raman spectrum of a CNT pellicle film, the G / D ratio, which is expressed as the ratio of the intensity of the G band to the intensity of the D band, is not particularly limited. However, from the viewpoint of suppressing variations in film thinning, it is preferably 40 or higher, more preferably 50 or higher, even more preferably 60 or higher, even more preferably 80 or higher, and even more preferably 100 or higher. There is no particular upper limit to the above G / D ratio; it may be 1000 or less, 500 or less, 300 or less, or 100 or less. The above G / D ratio, like the G / D ratio of raw material CNTs, is a value that is affected by the crystallinity. Therefore, for example, the above G / D ratio can be controlled by adjusting the crystallinity of the raw material CNTs. Specifically, the above G / D ratio can be increased by using CNTs as raw materials in which the overall crystallinity of the CNTs has been improved by using materials that can dissolve the less crystallinity portion. In addition, the above G / D ratio can be increased by controlling the manufacturing conditions of the CNT pellicle film. For example, the above G / D ratio can be increased by performing operations that improve the crystallinity of the CNT pellicle film.
[0067] -Method for evaluating the G / D ratio of CNT pellicle membranes- A CNT pellicle film is placed in a Raman microscope (e.g., XploRA manufactured by Horiba, Ltd.) as a measurement sample, and measurements are performed using a laser wavelength of 532 nm. From the obtained peaks, the G / D ratio is calculated from the intensities of the D band and G band, and this is defined as the G / D ratio of the CNT pellicle film. The D-band and G-band intensities of the CNT pellicle film are measured by Raman imaging using the CNT pellicle film. Similar to the G / D ratio of CNTs mentioned above, the intensity of the D band is such that the Raman shift is 1300 cm. -1 ~1400cm -1 This is the maximum value of Raman scattering intensity within the specified range. The intensity of the G-band is when the Raman shift is 1550 cm. -1 ~1610cm -1 This is the maximum value of Raman scattering intensity within the specified range. Multiple carbon nanotubes (CNTs) typically form bundles. The grain-to-density ratio (G / D) may be the minimum of the G / D values at seven locations within a predetermined bundle region in a cross-section of the CNT pellicle film cut along the axial direction of the bundle. The predetermined bundle region refers to the area within a bundle with a thickness of 10 nm or more, with a spatial resolution of 20 nm or less, in a 500 nm × 500 nm measurement area of the cross-section.
[0068] -G / D ratio reduction rate- Using the G / D ratio of carbon nanotubes, which is expressed as the ratio of the intensity of the G band to the intensity of the D band in the Raman spectrum of carbon nanotubes, and the G / D ratio of CNT pellicle films, which is expressed as the ratio of the intensity of the G band to the intensity of the D band in the Raman spectrum of carbon nanotube pellicle films, The G / D ratio reduction rate is not particularly limited by the following formula (2), but from the viewpoint of being able to expect chemical and thermal stability by fabricating a pellicle film without impairing the crystallinity of carbon nanotubes, it is preferably 85 or less, more preferably 80 or less, even more preferably 75 or less, even more preferably 70 or less, and even more preferably 65 or less. The lower limit of the above G / D ratio reduction rate may be 10 or more, 20 or more, 30 or more, or 40 or more. Equation (2): G / D ratio reduction rate = {(G / D ratio of carbon nanotubes) - (G / D ratio of CNT pellicle film)} × 100 / (G / D ratio of carbon nanotubes)
[0069] -Measurement of electrical resistivity- The electrical resistivity of the CNT pellicle film is not particularly limited, but from the viewpoint of avoiding charging of the CNT pellicle film, it is preferably 1 × 10⁻⁶. -7 Ω·cm~1×10 -3 It is Ω·cm, and more preferably 1 × 10⁻⁶ -6 Ω·cm~1×10 -3 It is Ω·cm, and more preferably 1 × 10⁻⁶ -4 Ω·cm~1×10 -3 It is Ω·cm. The electrical resistivity of the above-mentioned CNT pellicle film can be measured using a resistivity meter. Specifically, for example, it can be measured using the four-terminal method with a Loresta-GX (MCP-T700, manufactured by Nitto Seikou Analytech Co., Ltd.).
[0070] <Second carbon nanotube pellicle membrane> Another embodiment of the carbon nanotube pellicle membrane of this disclosure (hereinafter also referred to as the "second CNT pellicle membrane") is, Contains multiple carbon nanotubes, In the Raman spectrum of a carbon nanotube pellicle film, the G / D ratio, which is the ratio of the intensity of the G band to the intensity of the D band, is 40 or greater. The content of single-walled carbon nanotubes is 70% by mass or less of the total amount of carbon nanotubes. In the section titled "<Second Carbon Nanotube Pellicle Membrane>", the term "second CNT pellicle membrane" is also simply referred to as "CNT pellicle membrane".
[0071] Because the second CNT pellicle film has the above-described structure, variations in film thinning are suppressed. The reason why the second CNT pellicle membrane produces the above effect is not entirely clear, but it is presumed to be as follows. The inventors have found that by using CNTs with a large G / D ratio, which is expressed as the ratio of the intensity of the G band to the intensity of the D band in the Raman spectrum, it is easier to obtain a CNT pellicle film with a large G / D ratio, and that variations in film thinning are easily suppressed when a CNT pellicle film is obtained using such CNTs as a raw material. In other words, it is presumed that variations in film thinning can be suppressed when a CNT pellicle film having the above configuration is obtained. Furthermore, because the second CNT pellicle film contains the aforementioned single-walled carbon nanotubes, it also enhances the thermal and chemical stability of the CNT pellicle film.
[0072] (Etching rate of CNT pellicle film) In the case of CNT pellicle films, the etching rate when dry etching is performed by hydrogen plasma is preferably 0.40 nm / min or less, more preferably 0.38 nm / min or less, even more preferably 0.36 nm / min or less, even more preferably 0.34 nm / min or less, and even more preferably 0.32 nm / min or less, from the viewpoint of suppressing variations in film thinning and ensuring a sufficient number of uses for the pellicle film. The etching rate described above is preferable as it is low, and there is no particular lower limit to it, but it may be 0.05 nm / min or higher, 0.1 nm / min or higher, 0.15 nm / min or higher, or 0.2 nm / min or higher. The etching rate described above can be measured using the same method as the etching rate measurement method described in the section on the first CNT pellicle film.
[0073] (G / D ratio of CNT pellicle membrane) In the Raman spectrum of a CNT pellicle film, the G / D ratio, which is the ratio of the intensity of the G band to the intensity of the D band, is 40 or higher, preferably 50 or higher, more preferably 60 or higher, even more preferably 80 or higher, and still more preferably 100 or higher, from the viewpoint of suppressing variations in film thinning. There is no particular upper limit to the above G / D ratio; it may be 1000 or less, 500 or less, 300 or less, or 100 or less. The above G / D ratio can be evaluated using the same method as the evaluation method for the G / D ratio of the CNT pellicle film described in the section on the first CNT pellicle film.
[0074] (Content of single-walled carbon nanotubes) From the viewpoint of enhancing the thermal and chemical stability of the CNT pellicle film, the content of single-walled carbon nanotubes (WYSNs) among the multiple CNTs is 70% by mass or less, preferably 60% by mass or less, more preferably 50% by mass or less, even more preferably 30% by mass or less, and even more preferably 10% by mass or less, relative to the total amount of multiple CNTs. The lower limit of the single-walled carbon nanotube content described above is not particularly limited, but it may be greater than 0% by mass, 1% or more by mass, or 3% or more by mass.
[0075] For the second CNT pellicle film, conditions other than the etching rate, G / D ratio of the CNT pellicle film, and single-walled CNT content described above can be applied to the extent that they are applicable, as described for the first CNT pellicle film.
[0076] Hereinafter, the carbon nanotube pellicle film will be described using simply the term "carbon nanotube pellicle film" or "the carbon nanotube pellicle film of the present disclosure" without distinguishing between the first carbon nanotube pellicle film and the second carbon nanotube pellicle film. The following description of the carbon nanotube pellicle film can be applied to both the first carbon nanotube pellicle film and the second carbon nanotube pellicle film, unless otherwise specified.
[0077] <Method for Producing Carbon Nanotube Pellicle Film> There is no particular limitation on the method for producing the carbon nanotube pellicle film for either the first carbon nanotube pellicle film or the second carbon nanotube pellicle film described above, but the following Production Method A is suitable for the production of any of the carbon nanotube pellicle films. Production Method A is including a mixing step of mixing a plurality of carbon nanotubes and a solvent to obtain a dispersion liquid, In the Raman spectrum of the carbon nanotubes, the G / D ratio represented by the ratio of the G-band intensity to the D-band intensity is 200 or more. Production Method A may include steps other than the above-described mixing step.
[0078] (Mixing Step) Production Method A includes a mixing step of mixing a plurality of carbon nanotubes and a solvent to obtain a dispersion liquid. The dispersion liquid may be in a paste form as necessary. The method for mixing the dispersion liquid is not particularly limited, and examples thereof include a technique using cavitation (ultrasonic dispersion method), a technique of mechanically applying shear force (magnetic stirrer, ball mill, roller mill, vibration mill, kneader, homogenizer, etc.), or a technique using turbulent flow (jet mill, nanomizer, etc.), and the like.
[0079] -Carbon Nanotube- The dispersion liquid contains carbon nanotubes. As the carbon nanotubes, the carbon nanotubes described above can be used. Moreover, commercially available products can be used as the carbon nanotubes.
[0080] The amount of CNTs contained in the dispersion is not particularly limited, but is preferably 0.0001% to 10% by mass, more preferably 0.0001% to 1% by mass, and even more preferably 0.001% to 0.1% by mass, relative to the total amount of the dispersion.
[0081] -solvent- The dispersion contains a solvent. As a solvent, for example, carboxylic acids (COO - Examples include solvents having a hydroxyl group, solvents having a sulfone group, solvents having an amino group, esters, ketones, ethers, or aromatic hydrocarbons. Carboxylic acid (COO - Examples of solvents having a ) group include acetic acid or organic acids. Examples of solvents containing a hydroxyl group include water or alcohols. Examples of alcohols include methanol, ethanol, n-propanol, 2-propanol (also known as isopropanol or isopropyl alcohol), n-butanol, isobutanol, t-butanol, pentanol, hexanol, heptanol, octanol, nonanol, decanol, or amyl alcohol. Examples of solvents having a sulfone group include methyl sulfone, ethylphenyl sulfone, diethyl sulfone, diphenyl sulfone, sulfolane, bisphenol S, sorapsone, dapsone, bisphenol A polysulfone, or sulfolane. Examples of solvents containing an amino group include amide-type polar organic solvents, dimethylacetamide, or aminosilane. Examples of amide-type polar organic solvents include N,N-dimethylformamide or N-methylpyrrolidone. Aminosilane refers to a compound represented as H3SiNH2. Examples of esters include ethyl acetate or butyl acetate. Examples of ketones include acetone, methyl ethyl ketone, or cyclohexanone. Examples of ethers include diethyl ether, dioxane, or tetrahydrofuran. Examples of aromatic hydrocarbons include toluene, xylene, chlorobenzene, orthodichlorobenzene, or paradichlorobenzene. The solvent may be used alone or in a mixture of two or more types.
[0082] The solvent content in the dispersion is not particularly limited, but is preferably 90% to 99.9999% by mass, more preferably 99% to 99.9999% by mass, and even more preferably 99.9% to 99.999% by mass, relative to the total amount of the dispersion.
[0083] -Other ingredients- The dispersion may contain components other than CNTs and the solvent. Other components that may be contained in the dispersion besides CNTs and solvents include, for example, dispersants and other components that may be contained in the CNT pellicle film, as described in the "Other Components" section above.
[0084] The dispersant is not particularly limited as long as it can disperse CNTs and is soluble in the solvent used to disperse the CNTs. Examples of dispersants include surfactants, synthetic polymers, or natural polymers. Other components may be used individually or in combination of two or more.
[0085] Examples of surfactants include anionic surfactants, cationic surfactants, or nonionic surfactants. Specifically, examples of surfactants include polyacrylic acid, flavin derivatives, sodium dodecyl sulfate, sodium dodecyl sulfonate, sodium deoxycholate, sodium cholate, sodium dodecylbenzenesulfonate, sodium polyacrylate, or organic side-chain flavins. Examples of synthetic polymers include polyether diols, polyester diols, polycarbonate diols, polyvinyl alcohol, partially saponified polyvinyl alcohol, acetoacetyl-modified polyvinyl alcohol, acetal-modified polyvinyl alcohol, butyral-modified polyvinyl alcohol, silanol-modified polyvinyl alcohol, ethylene-vinyl alcohol copolymers, ethylene-vinyl alcohol-vinyl acetate copolymer resins, dimethylaminoethyl acrylate, dimethylaminoethyl methacrylate, acrylic resins, epoxy resins, modified epoxy resins, phenoxy resins, modified phenoxy resins, phenoxy ether resins, phenoxy ester resins, fluorine resins, melamine resins, alkyd resins, phenolic resins, polyacrylamide, polyacrylic acid, polystyrene sulfonic acid, polyethylene glycol, or polyvinylpyrrolidone. Examples of natural polymers include polysaccharides such as starch, pullulan, dextran, dextrin, guar gum, xanthan gum, amylose, amylopectin, alginic acid, gum arabic, carrageenan, chondroitin sulfate, hyaluronic acid, curdlan, chitin, chitosan, cellulose, or their salts or derivatives.
[0086] The dispersion preferably contains at least one selected from the group consisting of polyacrylic acid, flavin derivatives, sodium cholate, sodium deoxycholate, sodium dodecyl sulfate, sodium dodecylbenzenesulfonate, sodium polyacrylate, and organic side-chain flavins. This makes it easier for the CNTs to break down from clumps into individual fibers by stirring the dispersion (e.g., stirring with a stirrer). As a result, the variation in film thickness (roughness) of the unwashed CNT film formed by spin coating is smaller. Consequently, a CNT film with more uniform film thickness can be obtained.
[0087] In particular, the dispersion is more preferably polyacrylic acid. This ensures the flatness of the unwashed CNT film formed by spin coating. Furthermore, if the washing process includes a neutralization process described later, the CNT film peels off more easily from the hydrophilic substrate when immersed in the liquid.
[0088] If the dispersion contains components other than CNTs and the solvent, the amount of these components in the dispersion is not particularly limited, but is preferably 0.0001% to 10% by mass, more preferably 0.0001% to 1% by mass, and even more preferably 0.001% to 0.1% by mass, relative to the total amount of the dispersion.
[0089] (Coating film formation process) Method A may include a coating film forming step in which the dispersion obtained in the above mixing step is applied to a substrate to form a coating film. The method of applying the dispersion onto the substrate is not particularly limited and includes, for example, spin coating, dip coating, bar coating, spray coating, and electrospray coating. Among these, spin coating is preferred as the method of applying the dispersion. This makes it easier to control the desired film thickness by controlling the rotation speed, etc.
[0090] (Washing process) Method A may include a washing step in which the coating film formed in the above coating film formation step is washed to obtain a washed CNT pellicle film. The cleaning process can remove, for example, cleaning agents contained in the coating film. Specifically, if an acidic material is used as a dispersant, the dispersant can be neutralized and removed from the coating film by cleaning the coating film with an alkaline material.
[0091] (drying process) Manufacturing method A may include a drying step in which the coated film formed in the above-described coating film formation step, or the washed CNT pellicle film obtained in the washing step, is dried to obtain a dried CNT pellicle film. When the drying step is performed, in the separation step described later, the CNT film immersed in the liquid is more likely to peel off from the substrate and float on the liquid surface than when the drying step is not performed. The method for drying the above-mentioned film is not particularly limited and includes methods such as heating using a heating device or air drying. Examples of heating devices include hot plates, infrared lamps, ovens, or hot air dryers.
[0092] (separation process) Manufacturing method A may include a separation step for separating the coating film formed in the above coating film formation step, the washed CNT pellicle film obtained in the washing step, or the dried CNT pellicle film obtained in the drying step from the substrate. The method for separating the above-mentioned film from the substrate is not particularly limited. For example, one method involves immersing the substrate-attached CNT pellicle film in a liquid, causing the CNT pellicle film to detach from the substrate to float on the liquid surface. The liquid is not particularly limited as long as it can suspend the CNT pellicle membrane. Examples of liquids include water or aqueous solutions containing inorganic substances, and it is preferable that the liquid has an SP value of 35 or higher. The method for immersing the substrate-attached CNT pellicle film in liquid is not particularly limited and any known method is acceptable.
[0093] <Third Carbon Nanotube Pellicle Film> Another embodiment of the CNT pellicle film of this disclosure (hereinafter also referred to as the "third CNT pellicle film") is a film obtained by the above-described manufacturing method A, Contains multiple carbon nanotubes, In the Raman spectrum of carbon nanotubes (specifically, the Raman spectrum using carbon nanotubes as raw materials), the G / D ratio, which is the ratio of the intensity of the G band to the intensity of the D band, is 200 or more.
[0094] Because the third CNT pellicle film has the above configuration, variations in film loss between pellicle films are suppressed.
[0095] In the Raman spectrum of carbon nanotubes in the third CNT pellicle film, the G / D ratio, which is the ratio of the intensity of the G band to the intensity of the D band, is 200 or more, preferably 230 or more, more preferably 250 or more, and even more preferably 280 or more, from the viewpoint of suppressing variations in film thinning. The upper limit of the G / D ratio in the Raman spectrum of the carbon nanotube pellicle film described above may be, for example, 800 or less, 700 or less, 600 or less, 500 or less, or 400 or less. The above G / D ratio can be measured using the same method as the etching rate measurement method described in the section on the first CNT pellicle film.
[0096] In the third CNT pellicle film, the etching rate when dry etching is performed by hydrogen plasma is preferably 0.40 nm / min or less, more preferably 0.38 nm / min or less, even more preferably 0.36 nm / min or less, even more preferably 0.34 nm / min or less, and even more preferably 0.32 nm / min or less, from the viewpoint of suppressing variations in film thinning and ensuring a sufficient number of uses for the pellicle film. The etching rate described above is preferable as it is low, and there is no particular lower limit to it, but it may be 0.05 nm / min or higher, 0.1 nm / min or higher, 0.15 nm / min or higher, or 0.2 nm / min or higher. The etching rate described above can be measured using the same method as the etching rate measurement method described in the section on the first CNT pellicle film.
[0097] For the third CNT pellicle film, conditions other than the CNT G / D ratio and etching rate described above can be applied to the extent that they are applicable, as described for the first CNT pellicle film.
[0098] [Pericle] The pellicle of this disclosure includes a pellicle film of this disclosure and a pellicle frame for supporting the pellicle film. Since the pellicle of this disclosure comprises a CNT pellicle film of this disclosure, it provides the same effects as the CNT pellicle film of this disclosure.
[0099] The pellicle frame is a cylindrical object. The pellicle frame has an end face (hereinafter referred to as the "pellicle film end face") on one side in the height direction. The CNT pellicle film may be fixed to the pellicle film end face via an adhesive layer, or it may be fixed directly to the pellicle film end face. The adhesive constituting the adhesive layer is not particularly limited and includes, for example, acrylic resin adhesives, epoxy resin adhesives, polyimide resin adhesives, silicone resin adhesives, inorganic adhesives, double-sided adhesive tapes, polyolefin adhesives, and hydrogenated styrene adhesives. The term "adhesive" is a concept that includes not only adhesives but also tackeners. The thickness of the adhesive layer is, for example, 10 μm to 1 mm.
[0100] <Pellicle frame> The pellicle frame has exposure through-holes. These exposure through-holes indicate spaces through which light transmitted through the CNT pellicle film passes to reach the photomask.
[0101] The shape of the pellicle frame, measured from its height, is, for example, rectangular. This rectangular shape may be a square or a rectangle.
[0102] The pellicle frame may have ventilation holes. The ventilation holes are formed, for example, on the sides of the pellicle frame. The ventilation holes connect the internal space of the pellicle to the external space of the pellicle when the pellicle frame is attached to the photomask.
[0103] The rectangular pellicle frame, when viewed from the height direction, is composed of four sides. The length of one side in the longitudinal direction is preferably 200 mm or less. The size of the pellicle frame is standardized according to the type of exposure equipment. Having a length of 200 mm or less in the longitudinal direction of one side of the pellicle frame satisfies the standardized size for EUV exposure. The length of one side in the shorter direction is preferably 5 mm to 180 mm, more preferably 80 mm to 170 mm, and even more preferably 100 mm to 160 mm. The height of the pellicle frame is preferably 3.0 mm or less, more preferably 2.4 mm or less, and even more preferably 2.375 mm or less. This ensures that the pellicle frame meets the size standardized for EUV exposure. The height of the pellicle frame standardized for EUV exposure is, for example, 2.375 mm. The mass of the pellicle frame is not particularly limited, but is preferably 20g or less, more preferably 15g or less. This makes the pellicle frame suitable for EUV exposure applications.
[0104] The material of the pellicle frame is not particularly limited and may include quartz glass, metal, carbon-based materials, resin, silicon, and ceramic materials. Metals can be pure metals or alloys. Pure metals consist of a single metallic element. Examples of pure metals include aluminum and titanium. Alloys consist of multiple metallic elements, or a metallic element and a nonmetallic element. Examples of alloys include stainless steel, magnesium alloys, steel, carbon steel, and Invar. Examples of resins include polyethylene. Examples of ceramic materials include silicon nitride (SiN), silicon carbide (SiC), and alumina (Al2O3).
[0105] The structure of the pellicle frame may be a single piece or an assembled piece. A single piece is obtained by machining a single raw material sheet. An "assembled piece" is a combination of multiple components. Methods for integrating multiple components include using known adhesives and fastening components. Fastening components include bolts, nuts, screws, rivets, or pins. If the pellicle frame is an assembled piece, the materials of the multiple components may be different.
[0106] <Adhesive layer> The pellicle may further comprise an adhesive layer. The adhesive layer allows the pellicle to adhere to the photomask. The pellicle frame has an end face (hereinafter referred to as the "photomask end face") on the other side in the height direction. The adhesive layer is formed on the photomask end face. The adhesive layer is made of an adhesive resin. The adhesive resin is not particularly limited and includes acrylic adhesives, silicone adhesives, styrene adhesives, urethane adhesives, and olefin adhesives. The thickness of the adhesive layer is not particularly limited, but is preferably 10 μm to 500 μm.
[0107] <Embodiment> Next, an example of the pellicle of this disclosure will be described with reference to Figures 3 and 4. Figure 3 is a top view of the pellicle 10 according to the embodiment. Figure 4 is a cross-sectional view taken along line IV-IV in Figure 3.
[0108] As shown in Figure 4, the pellicle 10 comprises a CNT pellicle film 11, a pellicle frame 12, and an adhesive layer 13.
[0109] The CNT pellicle film 11 is the CNT pellicle film of this disclosure. The CNT pellicle film 11 contains a plurality of CNTs and unavoidable elements. The unavoidable elements include Fe. The Fe content is 5000 ppm by mass or less.
[0110] The CNT pellicle film 11 has a self-supporting region R (see Figure 3). The self-supporting region R is the part of the CNT pellicle film 11 that is not in contact with the pellicle frame 12. EUV is irradiated into the self-supporting region R.
[0111] The pellicle frame 12 is cylindrical. When viewed from the Z-axis direction, the pellicle frame 12 has a rectangular shape. The pellicle frame 12 has a through hole TH.
[0112] As shown in Figure 4, the pellicle frame 12 has a pellicle film end face S12A on the positive Z-axis side and a photomask end face S12B on the negative Z-axis side. The CNT pellicle film 11 is fixed to the pellicle film end face S12A of the pellicle frame 12 without an adhesive layer. An adhesive layer 13 is formed on the photomask end face S12B of the pellicle frame 12.
[0113] The adhesive layer 13 allows the pellicle 10 to be adhered to the photomask.
[0114] [Exposure plate] The exposure master of this disclosure comprises a photomask and a pellicle of this disclosure attached to the photomask. Since the exposure master plate of this disclosure is equipped with the pellicle of this disclosure, it produces the same effect as the pellicle of this disclosure.
[0115] The method for attaching the photomask to the pellicle is not particularly limited and includes methods using the adhesive layer described above, methods using fastening components, and methods utilizing the attractive force of magnets, etc.
[0116] The photomask comprises a support substrate, a reflective layer, and an absorber layer. Preferably, the support substrate, reflective layer, and absorber layer are stacked in this order. In this case, the pellicle is attached to the side of the photomask where the reflective layer and absorber layer are provided. The absorber layer partially absorbs EUV light, forming a desired image on the sensitive substrate (e.g., a semiconductor substrate with a photoresist film). Examples of reflective layers include multilayer films of molybdenum (Mo) and silicon (Si). The material of the absorber layer may be a highly absorbent material such as EUV light. Examples of highly absorbent materials such as EUV light include chromium (Cr) or tantalum nitride.
[0117] The exposure apparatus of this disclosure comprises an EUV light source that emits EUV as exposure light, an exposure master according to this disclosure, and an optical system that guides the exposure light emitted from the EUV light source to the exposure master. The exposure master is positioned so that the EUV emitted from the EUV light source passes through a pellicle film and irradiates the photomask. The exposure apparatus of this disclosure provides the same effects as the exposure master plate of this disclosure. Furthermore, because the exposure apparatus of this disclosure has the above configuration, it can form miniaturized patterns (for example, with a line width of 32 nm or less) and can perform pattern exposure with reduced resolution defects due to foreign matter.
[0118] A known EUV light source can be used. A known optical system can be used. [Examples]
[0119] The present disclosure will be described in further detail below based on examples. However, the present disclosure is not limited to these examples.
[0120] [Preparation of evaluation pellicle] <Comparative Example 1> (Coating film formation process) As raw material CNTs, several CNTs synthesized by the eDIPS method were used (brand: EC1.5, manufacturer: Meijo Nanocarbon Co., Ltd., tube diameter: 1nm~3nm, tube length: 100nm or more).
[0121] To 30 mg of multiple carbon nanotubes (CNTs), 70 mL of isopropyl alcohol and 30 mL of ethanol were added, and then 30 mg of polyacrylic acid was added as an additive. The mixture was stirred using a magnetic stirrer at 1000 rpm (revolutions per minute) at 40°C for 18 hours. The resulting suspension was then ultrasonically dispersed using a probe-type homogenizer at 40% output for a total of 30 minutes to obtain a CNT dispersion.
[0122] An 8-inch silicon wafer (hereinafter referred to as "silicon substrate") was prepared. A CNT dispersion was spin-coated onto the silicon substrate at a rotational speed of 1500 rpm. This resulted in a coated film being formed on the silicon substrate.
[0123] (Washing process) The coated film was alkaline-washed with tetramethylammonium hydroxide (hereinafter referred to as "TMAH") to remove polyacrylic acid from the coated film and then dried. This yielded a CCNT pellicle film.
[0124] Hereinafter, the silicon substrate and the CCNT pellicle film formed on the silicon substrate will be collectively referred to as the "film-coated silicon substrate."
[0125] (separation process) A silicon substrate with a film attached was immersed in a water bath. In the water, the CNT pellicle film was peeled off from the silicon substrate. The CNT pellicle film that was peeled off from the silicon substrate was left in the water, and the silicon substrate was removed from the water. At this time, the CNT pellicle film was floating on the water surface. As a result, a CNT pellicle film (film thickness: 34 nm) consisting of a CNT pellicle film with a mesh structure was obtained.
[0126] (Pellicle manufacturing process) A silicone frame (hereinafter also referred to as "pellicle frame") was prepared as the pellicle frame. The pellicle frame was cylindrical. The pellicle frame had a through hole. The through hole was formed along the height direction of the pellicle frame. As for the dimensions of the pellicle frame, a small piece of pellicle frame was prepared in which the outline of the through hole, viewed from one side in the height direction of the pellicle frame, was a square with sides of 10 mm. The CNT pellicle membrane floating on the water surface was scooped up with a small pellicle frame. This yielded an evaluation pellicle. The evaluation pellicle consisted of a pellicle frame and a CNT pellicle membrane placed on the pellicle frame. The CNT pellicle membrane of the evaluation pellicle was in contact with the pellicle frame and covered the entire area of the through-holes in the pellicle frame. No wrinkles were observed in the CNT pellicle membrane of the evaluation pellicle.
[0127] <Comparative Example 2> An evaluation pellicle was obtained in the same manner as in Comparative Example 1, except that the raw material CNTs were changed to multiple CNTs synthesized by the eDIPS method (brand: EC2.0P, manufacturer: Meijo Nanocarbon Co., Ltd., tube diameter: 1 nm to 3 nm, tube length: 100 nm or more) to obtain a CNT pellicle film (film thickness: 33 nm).
[0128] <Example 1> An evaluation pellicle was obtained in the same manner as in Comparative Example 1, except that the raw material CNTs were changed to multiple CNTs synthesized by the eDIPS method (brand: DX2, manufacturer: Meijo Nanocarbon Co., Ltd., tube diameter: 1 nm to 3 nm, tube length: 100 nm or more) to obtain a CNT pellicle film (film thickness: 34 nm).
[0129] <Example 2> An evaluation pellicle was obtained in the same manner as in Comparative Example 1, except that the raw material CNTs were changed to multiple CNTs synthesized by the eDIPS method (brand: DX3, manufacturer: Meijo Nanocarbon Co., Ltd., tube diameter: 1 nm to 3 nm, tube length: 100 nm or more) to obtain a CNT pellicle film (film thickness: 34 nm).
[0130] <Example 3> An evaluation pellicle was obtained in the same manner as in Comparative Example 1, except that the raw material CNTs were changed to multiple CNTs synthesized by the eDIPS method (brand: DX5, manufacturer: Meijo Nanocarbon Co., Ltd., tube diameter: 1 nm to 3 nm, tube length: 100 nm or more) to obtain a CNT pellicle film (film thickness: 33 nm).
[0131] [Measurement of the G / D ratio of carbon nanotubes] The etching rate of the CNT pellicle film was measured using the method described in the section "-Method for measuring the G / D ratio of carbon nanotubes-" in the section on embodiments for carrying out the above invention. The measurement results are shown in Table 2.
[0132] [Measurement of the G / D ratio of CNT pellicle membranes] The etching rate of the CNT pellicle film was measured using the method described in the section "-Method for measuring the G / D ratio of the CNT pellicle film-" in the section on embodiments for carrying out the above invention. For the above measurements, an XploRA Raman microscope manufactured by Horiba, Ltd. was used. The measurement results are shown in Table 2.
[0133] [Evaluation of the rate of decrease in the G / D ratio] The reduction rate of the G / D ratio was evaluated using the method described in the section "-Method for evaluating the reduction rate of the G / D ratio-" in the section on embodiments for carrying out the above invention. For the above measurements, an XploRA Raman microscope manufactured by Horiba, Ltd. was used. The evaluation results are shown in Table 2.
[0134] [Evaluation of the content of single-walled carbon nanotubes (WYNS) in multiple CNTs] In the section on "Modes for Carrying Out the Invention," specifically in the section on "-Method for Evaluating the Content of Single-Walled Carbon Nanotubes in Multiple CNTs-," the content of single-walled carbon nanotubes (hereinafter also referred to as the "single-walled carbon nanotube ratio") in multiple CNTs contained in an area of 3 μm × 3 μm was evaluated using a transmission electron microscope (Hitachi High-Tech Corporation: HF-2100). The evaluation results are shown in Table 2.
[0135] [Measurement of electrical resistivity] The electrical resistivity of the CNT pellicle film was measured using the method described in the section "-Measurement of electrical resistivity-" in the section on embodiments for carrying out the above invention. In the above measurements, a Loresta-GX (MCP-T700) manufactured by Nitto Seiko Analytech Co., Ltd. was used as the resistivity meter, and measurements were performed using the four-terminal method. The measurement results are shown in Table 2.
[0136] [Evaluation of etching rate] The etching rate of the CNT pellicle film was evaluated using the method described in the section "-Calculation of Etching Rate-" in the section on embodiments for carrying out the above invention. The thickness of the CNT pellicle film in this evaluation was measured using the method described in the section "-Method for Measuring Thickness-" in the section on embodiments for carrying out the above invention. In the above evaluation, the OPTM(A-1) manufactured by Otsuka Electronics Co., Ltd. was used as the micro-spectroscopic film thickness gauge, and the PDC-210 manufactured by Yamato Scientific Co., Ltd. was used as the parallel-plate plasma processing device. The evaluation results are shown in Table 2.
[0137] [Evaluation of etching rate variability] In each example and comparative example, a graph showing the correlation between the average G / D ratio and the etching rate was obtained, with the average G / D ratio of the carbon nanotubes on the horizontal axis and the etching rate on the vertical axis (hereinafter also referred to as the "G / D-etching rate correlation graph"). This graph is shown in Figure 5. Using the above G / D-etching rate correlation graph, the variation in etching rates was calculated using the following procedure. First, the slope of the line between each point and two adjacent points in the G / D etching rate correlation graph was calculated. If a line could be considered on both sides of each point, the slopes calculated on both sides of the point were averaged, and this average value was taken as the etching rate slope for that point. If a point is adjacent to only one side (either left or right), the slope of the line calculated on either side was taken as the etching rate slope for that point. Next, the standard deviation of the G / D ratio was calculated from the measurement results performed at multiple points (10,000 points) within the CNT pellicle film in each example and comparative example, assuming that the G / D distribution within the measurement area was a normal distribution. This value can be considered as the variation in the G / D ratio inherent in the raw material CNTs themselves. Then, by substituting the variation in the G / D ratio of each raw material CNT into the etching rate slope described above, it is possible to calculate the expected variation in etching rate from the variation in the G / D ratio inherent in the raw materials themselves. For each point, the absolute value of the product of the above G / D value standard deviation and the etching rate slope calculated from the G / D-etching rate correlation graph was evaluated as the etching rate variation for each point. The etching rate variation of Comparative Example 1 was normalized to 100, and the relative values of the etching rate variations of the other examples and comparative examples were calculated. The calculation results are shown in Table 2.
[0138] Typically, variations tend to occur in the G / D ratio of CNTs used as raw materials. When these variations occur, variations in the etching rate of each CNT pellicle film occur, that is, variations in film thinning occur from film to film. The small variation in the etching rate mentioned above means that differences in the CNTs used as raw materials (specifically, differences in the G / D ratio of the CNTs) have little effect on the etching rate. In other words, the smaller the variation in the etching rate, the less susceptible it is to variations in the CNTs used as raw materials (specifically, variations in the G / D ratio of the CNTs), and when multiple CNT pellicles are manufactured, the variation in film loss between multiple CNT pellicles is small.
[0139] In Table 2, a column marked "-" indicates that the corresponding characteristic has not been measured or evaluated.
[0140] [Table 2]
[0141] As shown in Table 2, the CNT pellicle films in Examples 1 to 3 that satisfy the configuration of the CNT pellicle film of this disclosure (i.e., the first CNT pellicle film, the second CNT pellicle film, or the third CNT pellicle film described above) showed less variation in etching rate compared to the CNT pellicle films in Comparative Examples 1 and 2 that did not satisfy any of the configurations of the CNT pellicle film of this disclosure. In other words, the CNT pellicle film of this disclosure made it possible to obtain a carbon nanotube pellicle film with suppressed variation in film wear per pellicle film. This can be expected to lead to a stable and long lifespan for the pellicle film. [Explanation of Symbols]
[0142] 10: Pellicle, 11: CNT pellicle film, 12: Pellicle frame, 13: Adhesive layer
Claims
1. Contains multiple carbon nanotubes, The etching rate when dry etching is performed using hydrogen plasma is 0.40 nm / min or less. Carbon nanotube pellicle membrane.
2. The carbon nanotube pellicle film according to claim 1, wherein the content of single-walled carbon nanotubes is 70% by mass or less of the total amount of carbon nanotubes.
3. The carbon nanotube pellicle film according to claim 1, wherein the G / D ratio, which is the ratio of the intensity of the G band to the intensity of the D band in the Raman spectrum of the carbon nanotube pellicle film, is 40 or more.
4. Contains multiple carbon nanotubes, In the Raman spectrum of a carbon nanotube pellicle film, the G / D ratio, which is the ratio of the intensity of the G band to the intensity of the D band, is 40 or greater. The content of single-walled carbon nanotubes is 70% by mass or less of the total amount of carbon nanotubes. Carbon nanotube pellicle membrane.
5. A pellicle comprising a carbon nanotube pellicle film according to any one of claims 1 to 4, and a pellicle frame for supporting the carbon nanotube pellicle film.
6. Photomask and The pellicle according to claim 5 attached to the photomask and An exposure master plate equipped with the following features.
7. An EUV light source that emits EUV (extreme ultraviolet light) as exposure light, The exposure plate described in claim 6, An optical system that guides the exposure light emitted from the EUV light source to the exposure plate, Equipped with, The exposure master plate is arranged such that the exposure light emitted from the EUV light source passes through the carbon nanotube pellicle film and irradiates the photomask.
8. The process includes a mixing step of mixing multiple carbon nanotubes and a solvent to obtain a dispersion. In the Raman spectrum of the carbon nanotube, the G / D ratio, which is the ratio of the intensity of the G band to the intensity of the D band, is 200 or more. A method for manufacturing carbon nanotube pellicle films.
9. In the Raman spectrum of the carbon nanotube, the G / D ratio of the carbon nanotube, which is expressed as the ratio of the intensity of the G band to the intensity of the D band, In the Raman spectrum of the carbon nanotube pellicle film, the G / D ratio of the carbon nanotube pellicle film, which is expressed as the ratio of the intensity of the G band to the intensity of the D band, is used. A method for producing a carbon nanotube pellicle film according to claim 8, wherein the G / D ratio reduction rate calculated by the following formula (2) is 85 or less. Equation (2): G / D ratio reduction rate = {(G / D ratio of carbon nanotubes) - (G / D ratio of carbon nanotube pellicle film)} × 100 / (G / D ratio of carbon nanotubes)
Citation Information
Patent Citations
Mask assembly
JP2020181212A